MicroRNA-208a Dysregulates Apoptosis Genes Expression and Promotes Cardiomyocyte Apoptosis during Ischemia and Its Silencing Improves Cardiac Function after Myocardial Infarction - Hasahya Tony; Kai Meng; Bangwei Wu; Aijia Yu; Qiutang Zeng; Kunwu Yu; Yucheng Zhong (Mediators of Inflammation)
Aims. miR-208a is associated with adverse outcomes in several cardiac pathologies known to have increased apoptosis, including myocardial infarction (MI). We investigated if miR-208a has proapoptotic effects on ischemic cardiomyocytes and if its silencing has therapeutic benefits in MI. Methods and Results. The effect of miR-208a on apoptosis during ischemia was studied in cultured neonatal mice myocytes transfected with agomir or antagomir. Differential gene expression was assessed using microarrays. MI was induced in male C57BL/6 mice randomly assigned to antagomir (n=6) or control group (n=7), while sham group (n=7) had sham operation done. Antagomir group received miR208a antagomir, while control and sham group mice received vehicle only. At 7 and 28 days, echocardiography was done and thereafter hearts were harvested for analysis of apoptosis by TUNEL method, fibrosis using Masson’s trichrome, and hypertrophy using hematoxylin and eosin. miR-208a altered apoptosis genes expression and increased apoptosis in ischemic cardiomyocytes. Therapeutic inhibition of miR-208a decreased cardiac fibrosis, hypertrophy, and apoptosis and significantly improved cardiac function 28 days after MI. Conclusion. miR-208a alters apoptosis genes expression and promotes apoptosis in ischemic cardiomyocytes, and its silencing attenuates apoptosis, fibrosis, and hypertrophy after MI, with significant improvement in cardiac function.